Bisphosphonate-related osteonecrosis of jaw의 치료에 대한 고찰 - 유경하(Kyung-Ha You); 윤규호(Kyu-Ho Yoon); 배정호(Jung-Ho Bae); 박재안(Jae-An Park); 박군찬(Gun-Chan Park); 신재명(Jae-Myung Shin); 백지선(Jee-Seon Baik); 정정권(Jeong-Kwon Cheong) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2010)
Bisphosphonates are widely used to treat osteoporosis, hypercalcemia of malignant tumor. Despite their clinical benefit, bisphosphonate-related osteonecrosis of the jaw (BRONJ) is a newly documented complication to patients receiving these drugs and first recognized by Marx in 2003. Thus,consideration of prevention and needs regarding unequivocal treatment regimen have emerged. Recently, several authors emphasized reports on appropriate clinical availability of surgical approach. It serves to concern about guideline for surgical and conservative treatment modalities. So, it is the purpose of this paper to review the current literatures about treatment regimens of BRONJ. KCI Citation Count: 1